Pengaruh Digital Dexterity Terhadap Kinerja Karyawan dan Kesediaan Karyawan untuk Terlibat dalam Kegiatan Pengembangan Usaha pada Peseroan Terbatas di Kota Batam - Mochammad Nugraha Reza Pradana; Santi, Santi (Program Studi Manajemen FEBM UMRAH, 2022)
The purpose of this study was to determine the effect of Digital Dexterity on employee performance and employee willingness in Limited Liability Companies in Batam City. The research approach used is a quantitative research approach. The sample in this study were employees who worked for companies in Batam City with a total population of 657,642 employees based on data from BPS Batam City in 2021. The data collection method used in this study was to use a questionnaire. The device used was SmartPLS version 3.3.9. In this study, there are two hypotheses proposed. Then, after processing the data, it is known that the two hypotheses can be accepted. The results of testing the first hypothesis (H1) show that the digital dexterity variable has a significant effect on the employee performance variable. Based on the answers from the respondents, it can be seen that Limited Liability Companies in Batam City apply digital dexterity in their companies and can affect the performance of their employees. The results of testing the second hypothesis (H2) show that the digital dexterity variable has a significant effect on the employee's willingness variable. Based on the answers from the respondents, it can be seen that Limited Liability Companies in Batam City apply digital dexterity in their companies and can affect the willingness of their employees